MODEL KOLABORASI SEKOLAH, KELUARGA DAN MASYARAKAT DALAM PENGUATAN KARAKTER RELIGIUS PESERTA DIDIK PADA LEMBAGA PENDIDIKAN ISLAM - Mulyadin; Darul Hikmi; Sri Fatmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to formulate a collaborative model between schools, families, and communities from an Islamic Education Management perspective as a strategy to strengthen the quality of Islamic education. This study employed a qualitative approach with library research methods through the review and synthesis of various relevant scientific literature. Data were obtained from accredited journals, academic books, and previous research on school-based management, educational partnerships, and community participation. Content analysis was used to develop an integrative conceptual framework. The study's findings indicate that effective collaboration requires participatory planning, ongoing communication, clear role allocation, and the strengthening of religious values ​​as a managerial foundation. The resulting model is conceptual in nature and requires further empirical testing to verify its effectiveness in various Islamic educational institution contexts.